The contribution of native aviation and space medicine into the medical and biological providing of the ﬁrst manned space ﬂight - I. V. Bukhtiyarov; M. N. Khomenko; I. V. Ivanov; A. I. Ivanov; S. L. Dzhergeniya; L. V. Zueva; N. I. Olenev; M. V. Polyakov; A. A. Shishov; E. V. Zharov (Сеченовский вестник, 2022)
The aim of this research is to estimate the contribution of aviation and space medicine in medical-biological preparation for the ﬁrst Yu.A. Gagarin’s space ﬂight and its signiﬁcance in medical higher education.